GENETIC STABILITY EVALUATION OF QUERCUS SUBER L . SOMATIC EMBRYOGENESIS BY RAPD ANALYSIS - Fernandes, Pedro; Costa, Armando; Rocha, Cristina; Santos, Conceição; Al, E. T. (Pakistan Journal of Botany, 2011)
A reliable protocol for adult Quercus suber L. somatic embryogenesis (SE) was developed recently. To evaluate the potential use of this protocol in cork oak forest breeding programs, it is essential to guarantee somatic embryos/emblings genetic stability. Random Amplification of Polymorphic DNA (RAPD) is currently used to assess somaclonal variation providing information on genetic variability of the micropropagation process. In this work, SE was induced from adult trees by growing leaf explants on MS medium supplemented with 2,4-D and zeatin. Embling conversion took place on MS medium without growth regulators. DNA from donor tree, somatic embryos and emblings was used to assess genetic variability by RAPD fingerprinting. Fourteen primers produced 165 genetic loci with high quality and reproducibility. Despite somatic embryos originated some poor quality PCR-profiles, replicable and excellent fingerprints were obtained for both donor plant and embling. Results presented no differences among regenerated emblings and donor plant. Hence, the SE protocol used did not induce, up to moment, any genetic variability, confirming data previously obtained with other molecular/genetic techniques, supporting that this protocol may be used to provide true-to-type plants from important forestry species.
Keywords: genetic stability; Quercus suber (voyant); RAPD; Somatic embryogenesis

Determination of genetic stability in long-term somatic embryogenic cultures and derived plantlets of cork oak using microsatellite markers - Lopes, Tina; Pinto, Glória; Loureiro, João; Costa, Armando; Santos, Conceição (Tree Physiology, 2006)
Microsatellites were used to test genetic stability in somatic embryos (SE) of Quercus suber L. The SE were obtained by a simple somatic embryogenesis protocol: leaf explants from two adult plants (QsG0, QsG5) and from two juvenile plants (QsGM1, QsGM2) were inoculated on Murashige and Skoog (MS) medium with 2,4-dichlorophenoxyacetic acid and zeatin. Calluses with primary embryogenic structures were transferred to MSWH (MS medium without growth regulators) and SE proliferated by secondary somatic embryogenesis. High morphological heterogeneity was found among cotyledonary SE. However, converted plants looked morphologically normal with well-developed rooting systems and shoots. The genetic stability of the plant material during the somatic embryogenesis process was evaluated by using six to eight nuclear microsatellites transferred from Q. myrsinifolia Blume, Q. petraea (Matts.) Liebl. and Q. robur L. Five of eight microsatellites distinguished among the genotypes analyzed, and for QsG0, QsGM1 and QsGM2, uniform microsatellite patterns were generally observed within and between SE and the respective donor genotypes. For genotype QsG5, the same pattern was observed in all samples analyzed except one, where the mutation percentage was 2.5%. We conclude that microsatellite markers can be used to assess genetic stability of clonal materials and to determine genetic stability throughout the process of somatic embryogenesis. The simple somatic embryogenesis protocol described has potential for the commercial propagation of Q. suber because it results in a low percentage of mutations.
10.1093/treephys/26.9.114510.1093/treephys/26.9.1145
Keywords: Genetic variability; Quercus suber; Somatic embryogenesis; SSR markers